Arduino Uno-Based Automatic Controller for Clothes Dryer Tool - Nasution, Intan Suhelfi; Rani, Selvia; Khairani, Khairani; Aini, Sarah; Sumarlin, Sumarlin; Sari, Sri Novida (Karya Techno Solusindo, 2024)
Abstract: Erratic weather changes cause continuous rain, so clothes that have been washed will take a long time to dry and become damp. The process is carried out in open air and requires quite a large space. The aim of this research is to design an Arduino Uno-based automatic clothes dryer that can dry clothes and determine the dryness level of clothes automatically. The research method used is research and development where the process of developing a clothes dryer system which previously used a heater is now perfected by using a light hair dryer and two fans. The results of testing the tool system begin with the time being set by an Arduino timer and the temperature being set by a humidity sensor. Keywords: Arduino Uno, Arduino Uno Controller, Automatic Controller, System Controller REFERENCES Aditya, L., & Wahyudin, D. (2021). LEMARI PENGERING PAKAIAN MENGGUNAKAN HEATER BERBASIS ARDUINO MEGA 2560. 9(2).Baco, S., Alamsyah, N., Maulani Arif, F., & Armida, S. (2022). Prototype Lemari Pengering Pakaian Dengan Suhu Panas Berbasis Arduino Uno. Jurnal Teknologi dan Komputer (JTEK), 2(01). https://doi.org/10.56923/jtek.v2i01.65Damawidjaya Biksono, S. (2022). Teknik Pengeringan Dasar. Deepublish.Fahmizal, S., Mayub, A., Kom, M., Arrofiq, I. M., & Ruciyanti, F. (2022). Mudah Belajar Arduino denganPendekatan berbasis Fritzing, Tinkercad dan Proteus. Deepublish.Fauzi, A., Aisuwarya, R., & Aisuwarya, R. (2020). Sistem Kendali Jarak Jauh dan Monitoring PenggunaanListrik pada Pompa Air melalui Smartphone. JITCE (Journal of Information Technology andComputer Engineering), 4(01), 32–39. https://doi.org/10.25077/jitce.4.01.32-39.2020 Hermansyah, H. A., Parinduri, I., & Hutagalung, M. H. J. E. (2020). Pembelajaran pada penerapan mikrokontroler AT8535, Arduino UNO R-3 Bascom AVR, Arduino UNO 1.16 dan FritzingElectronic Design. Medan: Yayasan Kita Menulis.Khakim, L. (2023). Buku Ajar Mikrokontroler ATMega 328. Penerbit NEM.Pangkey, J. N. D., Elim, I., & Rondonuwu, S. (2021). EVALUATION OF INTERNAL CONTROL SYSTEMCASH DISBURSEMENTS OF PT. BANK SULUTGO MAIN BRANCH.Shofiyullah, M., & Muharom, S. (n.d.). Sistem Pengering Pakaian Otomatis Berbasis Microcontroller. Wisaksono, A. (2019). Buku Ajar Pengantar Mikroprosessor. Umsida Press, 1–112.Yolanda, Y. (2022). Pengembangan Buku Elektronik (E-Book) Prakarya Elektronika Untuk MeningkatkanKeterampilan Abad 21 Terintegrasi Keterampilan Berpikir Kreatif Mahasiswa. PASCAL (Journal of Physics and Science Learning), 6(2), 93–106.